توظيف المحادثة اليوميّة في تنمية سرعة الكلام في المرحلة المتوسّطة لدى طلبة المدرسة التّربيّة الإسلاميّة جاندونج - يوليانتي, نلفي; فبريانتا, ريتا; يسرى, أوكتا رينا; حسنة, نور (ALSYSTECH Journal of Education Technology, 2023)
In this thesis, the author is looking for the effect of daily conversation on developing speaking skill. The purpose of this research is to use the daily conversation to teach the Arabic Language in the intermediate stage of the Islamic Education School Canduang. The researcher used the experimental. The researcher sampled 40 people, 20 in the experimental class and 20 in the control class. From the previous result, I found the effect on the education result in two class, students in the experimental class thet employs daily conversation found their results better and more beautiful than the control class that does not employ daily conversation. The arithmetic test is 3,536, as for result of the T as the above data should be known to known the significance of the difference between the two groups, if the sig. (2-tailed) tail is smaller than 0,05 it is 0,001, so there is a big difference. From the above data, there is the effect of daily conversation developing speaking skills in the middle stage among students of the Islamic Education School Canduang.